A Comparative Study of Open Cholecystectomy versus Laparoscopic Cholecystectomy in a Selected Hospital in Guwahati, Assam - Begum, Nazima; Deka, Roonmoni; Pratim Das, Partha (International Journal of Nursing Research, 2023)
Background: Cholelithiasis is a major cause of morbidity among Indians with a female preponderance. Open cholecystectomy (OC) used to be the surgical treatment for cholelithiasis. However, with the advent of laparoscopic cholecystectomy (LC), there has been a gradual shift in the treatment with most surgeons preferring LC over OC. Apart from the benefits of decreased hospital stay, lesser post-operative pain LC is also cosmetically better. Longer operative time and increased incidence of biliary leakage are some pitfalls of LC in initial phase of surgical practice. Aim: This study aims to compare OC with LC in selected hospitals in Guwahati, Assam. Objectives: The objective of the study was to evaluate the outcomes of with OC in relation to safety, efficacy, complications, cost, and satisfaction. Materials and Methods: It is a prospective randomized study of patients (500 each from LC and OC) having cholecystectomy aged between 13 and 81 years. Structured questionnaire was prepared for data collection. “Statistical analysis done in Excel Window 2010.” Results: The mean operation time for LC is 59.32 min and 69.22 min for OC (P < 0.001). The use of injectable analgesics in case of LC (mean number of days = 3.37) is considerably less than OC (mean number of days = 6.19). The conversion rate is 4.8%. Complication rate is higher in OC (17.9%) and in LC, it is 8.19%. Post-operative infection is 3.3% in LC and 7.5% in OC. Conclusion: LC is found to be better than OC in terms of post-operative pain, analgesic requirement, and early return to work.